Content of CD4+T cell subpopulations in predicting the efficacy of biological therapy for psoriasis in children - D. G. Kuptsova; T. V. Radigina; O. V. Kurbatova; A. I. Materikin; R. V. Epishev; L. A. Opryatin; A. A. Khotko; N. N. Murashkin; S. V. Petrichuk (Медицинская иммунология)
Psoriasis is a chronic inflammatory skin disease characterized by increased proliferation of epidermal cells, impaired keratinization and an inflammatory reaction in dermis caused by activation of T lymphocytes and synthesis of pro-inflammatory cytokines. The pathophysiology of psoriasis is also associated with a decrease in anti-inflammatory functions of immunosuppressive cells. Recently, there are more cases of development of resistance to ongoing therapy with biologics in children, requiring cancellation of drug or its replacement. The aim of the study was to evaluate the content of T helper subpopulations in prognosis of effectiveness of biologics in children with psoriasis. Immunophenotyping of T helper populations was performed in 110 children with psoriasis vulgaris before appointment of biologics, at 16 and 52 weeks. Age of children ranged from 6 to 18 years. Severity of psoriasis and effectiveness of therapy were assessed by index PASI, which varied 0-68. Content of Tregs, Thact and Th17 was determined by flow cytometry. In group with a sufficient effect of biologics, a decrease in PASI was obtained, both at week 16 of therapy (p = 0.000) and by year of treatment, p = 0.017. In children with psoriasis, regardless of duration and effectiveness of biologics, percentage of Thact was increased relative to normal values. In group 1 before prescription of biologics was increased percentage of Thact (p = 0.005) and Th17 (p = 0.001). Analysis of dynamics of content of small populations of T helper during 1 year of use of biologics in children with different efficacy of therapy showed that significant changes were found in content of Th17 and Treg, as well as their Th17/Treg. ROC analysis showed that when Th17 deviation was above 53%, Thact above 181% and Th17/Treg above 2.6 before biologics were prescribed, insufficient efficacy of therapy could be expected in 75% of cases by year. By the end of induction course, with a Th17 deviation above 102% and a Th17/Treg above 2.6, probability of ineffective treatment was already 82%. The study shows the informative value of assessment of Thact before appointment of biologics, dynamics of Th17 by the end of induction course and Treg after 16 weeks of therapy in prognosis of effectiveness of biologics in children with psoriasis.